The Impact of Technology Utilization on Employee Performance at the Regional Financial Agency of Solok Regency - Sari, Wiwi Widana; Iljasmadi, Iljasmadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the impact of information technology utilization on employee performance at the Regional Financial Agency (Badan Keuangan Daerah, BKD) of Solok Regency. The method used is quantitative with a survey approach, where data is collected through questionnaires, observations, and literature studies. Data analysis was conducted using simple linear regression to measure the relationship between technology utilization (X) and employee performance (Y). The results show that technology utilization significantly affects employee performance with a correlation coefficient (r) of 0.985, indicating a very strong relationship, and a coefficient of determination (R²) of 0.971, meaning that 97.1% of employee performance is influenced by technology utilization. The obtained regression equation is Y = 2.343 + 1.247X, indicating that an increase in technology utilization by one unit will increase employee performance by 1.247 units. Based on these results, it is recommended that the local government improve technology training, update infrastructure, and develop more integrated digital systems to enhance work efficiency and accountability in regional financial management.